Etika Komunikasi di Media Sosial Melalui Prinsip SMART (Salam, Ma’ruf, dan Tabayyun) Perspektif Al-Quran - Janah, Futihatul; Yusuf, Apriyadi (Universitas Islam Negeri Raden Intan Lampung, 2020)
The presence of social media platforms has had a positive impact in Indonesian society, namely the acceleration of information technology. The fast flow of information that is spread does not rule out the possibility that there are also a lot of information that have not been proven to be true, even this information is sometimes a Hoax, Sara Issue, also Hate Speech. With the spread of information quickly, it will certainly be very dangerous for all recipients of the information if they do not have good communication ethics in filtering news. The purpose of this study was to describe how anticipatory steps (principles of communication ethics) are incounter information received through social media. This research was used descriptive analysis method of literature by collecting information, theory through books, journals, documents, Qur'an, Hadith, and Tafsir. The result of this study was Islam has always taught the principles of communication ethics in social media, namely the principles of Qaulan ma'rufan, Qoulan Kariman, Qaulan Maysuran, Qoulan balighan, Qoulan layyinan, and Qoulan sadidan. In addition, the concept that can be applied in social media uses the concept of SMarT (Salam, Ma'ruf, Tabayyun), so that the information received is not misleading hoax information, sara issues that disturb the peace of the diversity of people - intolerant attitude among fellow people